ANALISIS KEPUASAN DAN KEPENTINGAN FASILITAS DAN LAYANAN ANGKUTAN BERBASIS ONLINE DI KOTA PADANG - Kurniati, Titi; Gunawan, Hendra; Nisya, Khairun (Jurnal Ilmiah Poli Rekayasa, 2023)
As a student city, the city of Padang is a residence for students from various regions. Limited public transportation in the city of Padang, students prefer to use online-based transportation for their mobility. This study aims to identify personal characteristics and travel experiences, satisfaction levels, and consumer interests of online-based transportation as a mode of transportation in the city of Padang. Research respondents are students and college students who study in the city of Padang. The online-based transportation used is Go-Jek. Data was collected through online questionnaire interviews. Data processing was carried out by descriptive statistical methods that described the characteristics of respondents, and statistical analysis of cross-tabulation was also carried out to find the level of influence between personal characteristics and travel experiences with online transportation. Analysis of the level of satisfaction and interest of online-based transportation consumers based on the Importance Performance Analysis (IPA) method. The average value of the level of satisfaction and consumer interest in aspects of service, reliability, comfort, security, and tariffs are 2.75 and 2.94, respectively. There are two attributes of facilities and services that are considered necessary. However, the level of service is not satisfactory, namely the availability of comfortable security devices for passengers and the availability of the fastest route.